Nitrogen mineralization and microbial activity as influenced by sulfur sources in an alkaline calcareous soil - Shah, Tufail; Shah, Zahir; Shah, Syed Atizaz Ali; Ahmad, Nazir (Journal of Scientific Agriculture, 2019)
A study was performed to check the effects of various sources of sulfur on microbial activity, microbial population, N mineralization and organic matter content in an alkaline calcareous soil by using soil samples collected from Malakandher Farm at 0-20 cm depth, and analyzed for microbial activity, total mineral nitrogen, bacterial and fungal population and organic matter content. The results showed that the rate of CO2 evolution and cumulative CO2 production were higher in soils amended with elemental sulfur followed by sulfuric acid and gypsum treated soils. The microbial activity decreased with incubation period in all treatments, and the microbial population was greatly affected by sulfur sources. Generally, the bacterial population decreased in soils amended with elemental sulfur, but the population was higher in soils amended with gypsum. Bacterial population was suppressed in soils treated with sulfuric acid. However, the fungal population was higher in soils amended with sulfuric acids was less in soil amended with elemental sulfur. The sulfur amendments promoted immobilization of N. The net N immobilized was higher in soil amended with gypsum followed by soils amended with sulfuric acid and elemental sulfur. The percent organic matter was higher in soils amended with gypsum and was decreased compared with that amended with elemental sulfur or sulfuric acid. These results suggested that soil microbiological properties changed with sulfur amendments during laboratory incubation.